Mental health in China change, tradition, and therapeutic governance - Yang, Jie 1970- (Polity, 2018)
"China's massive economic restructuring in recent decades has generated alarming incidences of mental disorder affecting over one hundred million people. This timely book provides an anthropological analysis of mental health in China through an exploration of psychology, psychiatry, psychotherapy and psychosocial practices, and the role of the State. The book offers a critical study of new characteristics and unique practices of Chinese psychology and cultural tradition, highlighting the embodied, holistic, heart-based approach to mental health. Drawing together voices from her own research and a broad range of theory, Jie Yang addresses the mental health of a diverse array of people, including members of China's elite, the middle class and underprivileged groups. She argues that the Chinese government aligns psychology with the imperatives and interests of state and market, mobilizing concepts of mental illness to resolve social, moral, economic, and political disorders while legitimating the continued rule of the party through psychological care and permissive empathy. This thoughtful analysis will appeal to those across the social sciences and humanities interested in well-being in China and the intersection of society, politics, culture, and mental health"...
Includes bibliographical references and index
Keywords: MEDICAL / Mental Health / bisacsh; Mental health -- China; Mental illness -- China; Mental health policy -- China; MEDICAL / Mental Health; Therapie; Psychische Störung; Psychische Gesundheit; China